The research of precipitation process of calcium carbonate from liquid wastes of soda manufacture - Михайлова, Євгенія Олександрівна; Ворожбиян, Михайло Іванович; Мороз, Микола Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with solving environmental problems of soda producing enterprises. A promising direction is developing low-waste technologies, which consist in processing wastes with obtaining products that are in great demand. As a commercial product, it is proposed to obtain chemically precipitated calcium carbonate, which is widely used as a filler to create various composite materials. The most bulky waste of soda ash production using ammonia process is distiller slurry, which is formed in an amount of 8-10 m3 per 1 ton of product and contains calcium ions. According to the results of complex theoretical and experimental studies, it is found that the best way to produce synthetic calcium carbonate is its precipitation from distiller liquid (clarified part of distiller slurry) using carbonate ion-containing solutions. Excessive mother liquor of purified sodium bicarbonate production or sodium carbonate solution with a predetermined concentration can be used as precipitant. The paper presents the results of studies of the dependence of precipitation degree and basic physicochemical characteristics of calcium carbonate on the process parameters. Process conditions (temperature, reaction time, the ratio of reactants), which allow to obtain a product that meets modern requirements for filler, are defined.